The Relationship Between Permissive Parenting Styles dan Promiscuity Among High School Students - Asiah; Delima Gustina Manullang; Rafael Lisinus Ginting; Erwita Ika Violina (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to determine the relationship between permissive parenting styles and promiscuity among tenth-grade students at SMA Negeri 18 Medan. The research approach used is quantitative with a correlational method. The sampling technique used is purposive sampling, with a total of 69 respondents from a total population of 230 students. The results of the data analysis indicate a significant positive correlation between permissive parenting styles and free-wheeling social behavior. The higher the level of permissive parenting applied by parents, the higher the tendency for students to engage in promiscuity. This is indicated by the coefficient of determination (r²) value of 0.674, meaning that permissive parenting contributes 45.43% to promiscuous behavior. The remainder is influenced by other factors such as self-control, family economics, and social environment. Descriptively, permissive parenting is predominantly in the moderate category (62.3%), with the main aspect being a lack of parental attention to the child's responsibilities, social interactions, and personal issues. Free-wheeling behavior is also in the moderate category (71.0%), with dominant factors including the influence of mass media, social environment, and personal motivation. These findings highlight the importance of active parental involvement in guiding adolescent development to prevent deviant behavior.